IMPLEMENTASI EDUTAINMENT DALAM PEMBELAJARAN AL-QUR’AN BAGI SISWA SDIT MUTIARA CENDEKIA LUBUKLINGGAU - Yesi Arikarani (El-Ghiroh : Jurnal Studi Keislaman, 2017)
This modern development is always challenge human to always think and creat until new inovation. a various of life included in al-Qur’an learning. The word of education and learning this mark phenomenon with various strategy, method, model, although new approachment as, quantum learning, active learning, contextual teaching and learning (CTL) and another included edutainment. The field phenomenon is a implementation edutainment al-Qur’an learning in Islam integrated elementary school (SDIT) Mutiara Cendekia Lubuklinggau have criteria learn covering read, write, and memorize. The game criteria al-Qur’an learning. When one of game cause happines but do not obtain certain skills, then game is not an element of education. Conversely, if the activites of learning al-Qur’an but no element of happiness, it’s not called the game.therefore edutainment in al-Qur’an learning how about can integrate both of them well until can reaching the purpose learning wich are desired.